Modelling store operated calcium entry: creating a three dimensional spatio-temporal model to predict local calcium signals - McIvor, Emma (2018)
Calcium is a signalling messenger that is crucial to cellular function, controlling a diverse range of processes such as apoptosis, cell proliferation and muscle contraction. Store operated calcium entry (SOCE) is a specific pathway coupling depletion of the calcium stores within the endoplasmic reticulum (ER) to calcium influx through Orai channels on the plasma membrane. SOCE occurs in small sub-cellular regions called 'ER-PM junctions' which are typically less than $300$nm in diameter. The small size of these domains prevent direct measurement of the calcium signals as current calcium imaging techniques cannot resolve the local signals within ER-PM junctions. The calcium signals associated with SOCE control many downstream cellular processes, such as gene expression and immune responses. There is substantial evidence demonstrating that the placement of the calcium signalling machinery, including Orai channels and SERCA pumps, is vital to the generation of spatially distinct calcium signals which then enhance the selectivity of the calcium signal. However, experimental techniques cannot investigate the local calcium dynamics occurring on a spatial scale of micrometres so mathematical modelling techniques can be used to close this gap in understanding how the local calcium dynamics affect the experimentally observed global calcium dynamics.